PERSEPSI WARGA BELAJAR TERHADAP PELAKSANAAN PEMBELAJARAN PAKET C DI PKBM BUNGA TANJUNG KABUPATEN KAMPAR - ', Maizal; Jas, Jasfar; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on the state of facilities and in the implementation of the learning package c in PKBM It can be said support, although not memadai.rumusan problems research is whether perception residents learn with the implementation of the learning package c in PKBM Bunga Tanjung Kabupaten Kampar in good?. The purpose of this research is to find perception residents learn with the implementation of the learning package C PKBM Bunga Tanjung Kabupaten Kampar in good. Population in this study 60 people learn. So research sample areas 38 people and the other 20 sample test on critical level 10 %, sample used is simple random sampling. An instrument data collection that is chief with 50 a statement and if the trial live 47 a statement valid for in made instrument research. Data analysis through descriptive analysis quantitative. The results of the analysis that have been conducted by then a conclusion can be drawn to the result of this research be seen that, perception residents learn with the implementation of the learning package c in PKBM Bunga Tanjung Kabupaten Kampar in good, with the 77 %. Although environmental factors are more dominant than factors instrumental. It means residents learn thought that environment around and place study in PKBM Bunga Tanjung be able to support learning as expected.Key words: Perception, perception residents learning